Nostalgia, Memory, and Politics in Chilean Documentaries of Return - Traverso, Antonio (Fairleigh Dickinson University Press, 2013)
Despite the deep personal resonances and historical significance found in Chilean post-dictatorship fiction cinema, it has been documentary filmmakers who have most readily and extensively embraced the public memory project in this South American country. This chapter discusses a series of political documentaries that frontally address the hotly debated theme of the military dictatorship (1973-1990). The chapter considers the notion of "documentary of return" (Walker) vis-a-vis ideas derived from the theorization of nostalgia, and seeks to contribute to debates about the social function and cultural value of cinematic engagements with the memory of the Chilean historical disaster.